Students' Perceptions of The Use of The Quizlet Application in Their Reading - wilda anwar, hazril fikri; Ismahani, Siti (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to explore students’ perceptions of using the Quizlet application inenhancing their reading abilities, as well as to identify the benefits and challenges theyencounter during the learning process. The background of this research stems from thelow reading interest among students and the growing need for integrating engaging educational technologies into language learning. A qualitative method with aphenomenological design was employed, involving four ninth-grade students from ajunior high school in Medan City selected through purposive sampling. Data were collected through observation, questionnaires, and in-depth interviews, then analysed using thematic analysis. The findings reveal that students perceive Quizlet positively,Mhighlighting its effectiveness in improving reading comprehension through interactive features such as flashcards, audio, and game modes. The application contributes to vocabulary development, enhances motivation, and supports flexible learning. However, challenges such as limited internet access, difficulty operating certain features, and digital distractions were also reported, suggesting the need for appropriate guidance and strategies in utilizing digital learning tools effectively.